Simulation of an ideal quantum computer on a supercomputer ’Lomonosov’ - Korzh, O.V.; Korobkov, S.V.; Andreev, D.Yu.; Korzh, A.A.; Chernyavskiy, A.Yu. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2013)
One of the problems whose solution is expected to be available by exaflops supercomputers is to build a computer based on new principles that will provide a significant progress in computing speed. This paper presents a simulation of an ideal quantum computer on a supercomputer «Lomonosov». An efficient algorithm for parallel computations of one-, two- and three-qubit transformations is proposed. This algorithm uses DISLIB. As an example, the quantum Grover algorithm and the quantum Fourier transform are considered.